Theoretical and experimental investigation of magnetic field related helium leak in helium vessel of a large superconducting magnet. (June 2017) - Bhattachryya, Pranab; Gupta, Anjan Dutta; Dhar, S.; Sarma, P.R.; Mukherjee, Paramita
Highlights: Superconducting magnet faces degradation of insulation vacuum with current. Equation proposed to fit experimental data of insulation vacuum with current. Stress analysis explains impact of particular coil on vacuum degradation. Estimated leak size at no current based on experimental and MSLD data. Offered model of leak enhancement with current is consistent with experiment. Abstract: The helium vessel of the superconducting cyclotron (SCC) at the Variable Energy Cyclotron centre (VECC), Kolkata shows a gradual loss of insulation vacuum from 10 −7 mbar to 10 −4 mbar with increasing coil current in the magnet. The insulation vacuum restores back to its initial value with the withdrawal of current. The origin of such behavior has been thought to be related to the electromagnetic stress in the magnet. The electromagnetic stress distribution in the median plane of the helium vessel was studied to figure out the possible location of the helium leak. The stress field from the possible location was transferred to a simplified 2D model with different leak geometries to study the changes in conductance with coil current. The leak rate calculated from the changes in the leak geometry was compared with the leak rate calculated from the experimental insulation vacuum degradation behavior to estimate the initial leak shape and size.